Safety of Andrographis paniculata: A systematic review and meta-analysis - Wiwan Worakunphanich (2022)
Purpose: Andrographis paniculata is one of the commonly used herbal medicines worldwide. Nevertheless, evidences on adverse events (AEs) associated with Andrographis paniculata are very limited. This systematic review and meta-analysis was conducted to estimate and to compare the AE incidence of oral monotherapy Andrographis paniculata with others among patients with upper respiratory tract infection, noninfective diarrhea, and autoimmune disease. Methods: Systematic search was performed through six databases from inception until August 2018. Randomized controlled trial (RCT), cohort, or intensive monitoring of AEs was eligible for review if AE incidence was examined. The incidence of AEs was, then, pooled across studies using meta-analysis. Results: Ten RCTs and 3 intensive monitoring studies were included. Incidence of serious AEs was very rare with the pooled incidence (95% CI) from RCTs of 0.02 per 1000 patients (0.0–0.5). However, the incidence of nonserious AEs was considered very common with the pooled incidence (95% CI) from RCTs of 102.6 per 1000 patients (10.7–256.1), and the pooled incidence (95% CI) from intensive monitoring of 34.2 per 1000 patients (0.0–229.6). The most common nonserious AEs were related to gastrointestinal disorder, and skin and subcutaneous disorder system. Conclusions: Like other medicine, Andrographis paniculata can cause some AEs. However, it may be generally safe. Nevertheless, prospective patients who plan to use Andrographis paniculata should be thoroughly advised and closely monitored for common AEs. Due to the increasing use of Andrographis paniculata worldwide, larger studies with adequate methodological quality are warranted to monitor the safety of such product.